O ato de fé como dinamismo de conversão - Duque, João Manuel (Revista eclesiástica brasileira, 2007)
The objective of the present article is to outline a theology of the Christian faith focusing in particular on the relationship between the act of faith and the dynamics of conversion. If conversion implies guiding the human being towards his/her truth and towards the truth of the entire historical-social process, a similar claim can be made about the act of faith. On this assumption, the author analyses the act of faith viewing it as the constitution of the subject and of social relations that contrast with the modern pretensions of self-justification and the nihilist effects of post-Modernity. Thus, the faith becomes the basis for a personal and social identity that starts in the other and goes towards the other. From this arise the unavoidable theological, ecclesial and pragmatic-social dimensions of the act of faith without which it would not be the genuine source of energy for conversion and salvation.